2019
DOI: 10.1136/bmjoq-2018-000377
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of adverse events to death of hospitalised patients

Abstract: BackgroundThere is no standardised method to investigate death as a patient safety indicator and we need valid and reliable measurements to use adverse events contributing to death as a quality measure.ObjectiveTo investigate the contribution of severe adverse events to death in hospitalised patients and clarify methodological differences using the Global Trigger Tool method on all inpatient deaths compared with a sample of general hospitalised patients.MethodRetrospective records reviewing using the Global Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“…In the United States, medical errors account for more than 250,000 deaths a year, making it the third leading cause of death [1]. A study conducted in Norway has identified that patients who die in hospitals experience seven times the rate of serious adverse events [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, medical errors account for more than 250,000 deaths a year, making it the third leading cause of death [1]. A study conducted in Norway has identified that patients who die in hospitals experience seven times the rate of serious adverse events [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, because of the high prevalence of burnout among health workers due to the increasing number of adverse events [1,2,3,4,5,6,7,8,9,10], the following question arises: What is the relationship between burnout and patient safety?…”
Section: Introductionmentioning
confidence: 99%
“…16 Patients that die in hospital experience seven times the rate of AEs compared to those that do not die. 26 Reviewing inpatient deaths with the GTT may therefore provide new insight in causes of adverse events that contribute to death.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate malpractice litigation, the relevant data, especially related to hospital injuries, required that the Harvard Medical Malpractice Study develop a standardized approach to chart review. 34,35 This endeavor resulted in insights about adverse event causation and lead to the initiation of root cause analysis. 3,28,36 The trigger tool methodology was developed where medical records were used to identify potential or actual adverse events during patient care, a process that is now largely automated.…”
Section: Discussionmentioning
confidence: 99%